COLLEGIATE BODY, WHICH PROVIDES GENERAL GOVERNANCE OF THE UNIVERSITY (from history of the Plekhanov Russian University of Economics) - Antonina S. Fomina; Marina I. Skripnikova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with functioning of the in-university governance body, i. e. the Academic Council of the Russian Plekhanov University of Economics. In comparison with competence and obligations of the present day Academic Council the authors investigate specific features of Plekhanovka Council functioning during shaping and developing the soviet model of higher education (the 1930-s – early 1940-s). By analyzing the normative documents we can come to the conclusion about extending the Council’s responsibility in terms of general governance, training and certification of the faculty, in the field of academic and teaching work and at the same time about intensifying the administrative control on the part of soviet leadership. The article points out to promising directions in researching in-university governance, the Academic Council functioning, including that in Plekhanovka.